2011
DOI: 10.1039/c0cc04812g
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation and upconversion luminescence of graphene quantum dots

Abstract: A facile hydrazine hydrate reduction of graphene oxide (GO) with surface-passivated by a polyethylene glycol (PEG) method for the fabrication of graphene quantum dots (GQDs) with frequency upconverted emission is presented. And we speculate on the upconversion luminescence due to the anti-Stokes photoluminescence (ASPL), where the δE between the π and σ orbitals is near 1.1 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
553
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 773 publications
(588 citation statements)
references
References 32 publications
31
553
2
2
Order By: Relevance
“…Graphene quantum dots (GQDs) have been synthesized or fabricated from various carbon-based materials including fullerene 13 , glucose 14 , graphite or graphene oxides [15][16][17][18][19][20][21][22][23] , carbon nanotubes 24 and carbon fibres 25 . Physical approaches such as lithography 26 , which etch the size of graphene to B20 nm in width, are expensive and are impractical for the production of bulk quantities of material.…”
mentioning
confidence: 99%
“…Graphene quantum dots (GQDs) have been synthesized or fabricated from various carbon-based materials including fullerene 13 , glucose 14 , graphite or graphene oxides [15][16][17][18][19][20][21][22][23] , carbon nanotubes 24 and carbon fibres 25 . Physical approaches such as lithography 26 , which etch the size of graphene to B20 nm in width, are expensive and are impractical for the production of bulk quantities of material.…”
mentioning
confidence: 99%
“…[11][12][13][14] Recently, it has been found that besides the traditional down-converted photoluminescence, CQDs also display excellent up-converted photoluminescence (UCPL), in which the emission wavelength is shorter than the excitation wavelength used. 15,16 Moreover, photoexcited CQDs can also act as excellent electron acceptors and electron donors, as the PL from CQDs can be quenched e±ciently by either electron donor or electron acceptor molecules in solution. 17,18 Therefore, the unique UCPL behavior of CQDs allows for the full exploitation of the solar light, although the photo-induced electron transfer property can facilitate the charge separation rate of CQDs/semiconductor composites.…”
Section: Introductionmentioning
confidence: 99%
“…[234][235][236] In addition, GQDs possess unique optical properties such as pH-dependent and upconversion fluorescence behaviors, and GQDs are extensively used for cellular imaging in cells, organs, or tissues in this region. 237,238 Recently, Chen et al 239 reported the synthesis of composites of dextran-coated Fe 3 O 4 NPs and GO (Fe 3 O 4 -GO) as T2-weighted contrast agents for efficient cellular magnetic resonance imaging (MRI). Squaraine dyes were loaded inside mesoporous silica NPs, and the NP surfaces were then wrapped with ultrathin GO sheets; the resulted product exhibited remarkable stability and efficiently protected the loaded dye from nucleophilic attack.…”
mentioning
confidence: 99%